Society’s Religiosity in Social Media and Its Implications for Conflict Resolution in Indonesia - Doli Witro; Halil Khusairi; Nurul Alamin; Luqyana Azmiya Putri; Restu Prana Ilahi (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
Indonesian people who have religious and cultural diversity are considered capable of showing religiosity in conflict resolution between religious communities and being a peacemaker that occurs on social media. However, it cannot be denied that, in reality, during a peaceful society with various religions, conflicts still occur with various causes and effects. So, in the end, the conflict can become a negative side and a threat to the religiosity factor. This article aims to discover how one’s religiosity can affect conflict resolution on social media. This article uses a library research method. Sources of data obtained by materials that are library. The data analysis technique used is data condensation, data presentation, and conclusion drawing. The results show that the religiosity of the Indonesian people will be better if conflict resolution is built on the teachings of religion itself. Every religion does not teach conflict because if there is a high level of religiosity, everyone will feel safe, comfortable, and peaceful.